Integrating Situations into a Theory of Discourse Anaphora - Milward, David (Proceedings of the Amsterdam Colloquium, 1995)
This paper provides an account of definite and pronominal anaphora which draws together insights from dynamic semantics and situation semantics. The result is a dynamic semantics in which contexts consist of the parts of a scenario which have been brought to a hearer 's attention. The contexts are structured by meta-level disjunction, corresponding to a set of situations where one is in attention but the hearer doesn't know which one, and meta-level conjunction corresponding to a set of situations which are simultaneously in attention. Data from bridging reference, disjunction, and telescoping is used to motivate the account, together with some of the data which has been used in the past to argue for and against situation based accounts of anaphora.